Estudo dos parâmetros físico-químicos e sensoriais de sorvete de acerola (Malpighia glabra L.) submetido ao congelamento rápido (-80°C) e lento (-18°C) - Vieira, Anne Caroline Almeida (2013)
The ice creams are made from an emulsion stabilized by a process that beating and freezing produces a creamy substance, soft and pleasing to the palate. The emulsions are composed of milk products, water, fat, sugars, stabilizers, flavoring agents and others. The aim of this work was to study the effect of the processes of slow freezing (-18°C) and deep freezing (-80°C), evaluating the physico-chemical, nutritional and sensory acceptance of ice cream prepared with pulp acerola (Malpighia glabra L.) in relation sensory analysis of the ice cream acerola frozen at -80°C had higher grades and took the preference of 60 untrained panelists. The chemical composition of the ice acerola was within the values established by law and analysis overrun with 110% value that identifies the ice cream as good quality. In the melt, it was observed that the ice cream frozen retained its structure and shape for longer, compared to conventional ice cream. A greater stability of frozen ice cream compared to conventional ice cream, as demonstrated by the test melting